Empowerment and self-efficacy in patients with chronic disease; a systematic review study - Ali Hasanpour Dehkordi; Emad Zare Dehabadi; Mohammad Reza Rezaei; Ayda Hasanpour Dehkordi; Farinaz Fattahi; Aisan Ghasemi Oskui; Sam Mirfendereski; Farshad Yadollahi; Hamidreza Khodabandeh; Majid Sadeghpour (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: It is crucial for patients with chronic disease to learn the skills they need to manage their illnesses, which is called empowerment. Objectives: This review study aimed to evaluate the need for empowerment and self-efficacy in patients with chronic disease. Methods: The keywords were looked up in articles published between 2014 and 2023 using electronic databases, including Web of Science, PubMed, Embase, Scopus, and the search engine Google scholar. All obtained pertinent papers and books were analyzed based on the search method and the established criteria, and all redundant and unrelated items were excluded. Results: Results showed that empowerment and self-efficacy were conducted as a technique or strategy to guide patients and caregivers. An empowerment and self-efficacy model can promote quality of life (QoL) in chronic disease patients. Despite empowerment being beneficial for patients with chronic illnesses in previous studies, it should also be implemented for patients with other diseases. Conclusion: Given this literature results, the empowerment and self-efficacy model can improve the QoL in patients with chronic illnesses. Registration: This study has been compiled based on the PRISMA checklist, and its protocol was registered on the PROSPERO website (ID: CRD42023417639).